Influence of Arbuscular Mycorrhizal Fungi on the Initial Growth of Three Economically Important Forest Species in Ecuador - Prieto-Benavides, Oscar Oswaldo; Jiménez-Romero, Edwin Miguel; Crespo-Gutiérrez, Rommel Santiago; Arellano-Ibarra, Ketty Vanessa (REVISTA TERRA LATINOAMERICANA, 2025)
In recent years, the excessive use of chemical inputs in agriculture has generated negative environmental consequences, such as soil contamination and biodiversity loss, which has increased interest in ecological fertilization as a sustainable alternative. This study evaluates the ef fects of biofertilization with arbuscular mycorrhizal fungi (AMF) on the initial growth of three economically important forest species in Ecuador: white guayacan (Cybistax donnell-smithii Rose), pachaco (Schizolobium parahybum), and laurel (Cordia alliodora). Variables such as mycorrhizal colonization, spore density in the soil, and plant growth in terms of height, diameter, and biomass were evaluated. The results showed that AMF treatments significantly increased mycorrhizal colonization and spore density compared to the control. The liquid inoculum obtained the best results, with 5.84% colonization in pachaco, 3.72% in laurel, and 3.12% in white guayacan. Additionally, spore density was higher in the liquid inoculum treatment, recording 163 spores in pachaco, 128 in white guayacan, and 112 in laurel. Plants treated with AMF also exhibited greater height, diameter, and biomass. Pachaco treated with liquid inoculum reached an average height of 156.6 cm, a diameter of 7.24 mm, and a fresh aerial biomass of 1411 g. However, limitations were identified related to the variability of response among species and the need for controlled conditions to maximize benefits. This study highlights the originality and value of using AMF as biofertilizers, demonstrating their potential to improve sustainability and ef ficiency in forest production. In conclusion, biofertilization with AMF can be an ef fective strategy to promote the growth and adaptation of forest species in nurseries, thus contributing to more sustainable and environmentally beneficial agricultural practices.